Brassinosteroid Enhances Cucumber Stress Tolerance to NaHCO3 by Modulating Nitrogen Metabolism, Ionic Balance and Phytohormonal Response - Wenjing Nie; Biao Gong; Dan Wen; Peng Qiao; Hongen Guo; Qinghua Shi (Plants)
Under NaHCO3 stress, exogenous 24-epibrassinolide (EBR) markedly alleviated Na+ accumulation in cucumber plants, thereby decreasing the Na+/K+, Na+/Mg2+, and Na+/Ca2+ ratios. This mitigation was accompanied by elevated concentrations of K+, Ca2+, and Mg2+, as well as enhanced expression of the NHX and SOS1 genes. In addition, the activities of plasma membrane H+-ATPase, vesicular membrane H+-ATPase, and vesicular membrane H+-PPase were significantly increased, contributing to the maintenance of ionic balance in cucumber plants. NaHCO3 stress disrupted nitrogen metabolism, as evidenced by reductions in the activities of NR, GS, GOGAT, GOT, and GPT, along with altered GDH activity. These disruptions led to an accumulation of NH4+ and substantial decreases in NO3−-N and total nitrogen content. Exogenous EBR alleviated these effects by enhancing the activities of NR, GS, GOGAT, GOT, and GPT, countering the prolonged suppression of GDH activity, and restoring NO3−-N and total nitrogen levels. Consequently, EBR application reduced NH4+ toxicity induced by alkali stress. Additionally, NaHCO3 stress increased ABA accumulation while decreasing IAA and GA3 content in cucumber seedlings. In contrast, exogenous EBR application elevated IAA and GA3 levels and increased the IAA/ABA and GA3/ABA ratios, thus maintaining hormonal equilibrium under alkali stress. Collectively, these findings highlight that exogenous EBR enhances the alkaline tolerance of cucumber plants by regulating nitrogen metabolism, ion homeostasis, and phytohormonal responses.